THE INFLUENCE OF CORPORATE IMAGE AND PERCEIVED VALUE TO CUSTOMER SATISFACTION (STUDY AT WEDDING ORGANIZER IN MANADO) - Johanis, Kelly; Rumokoy, Farlane S.; Tumiwa, Johan (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Purpose of this study are to determine the influence of corporate image, and perceived value to customer satisfaction for the Wedding Organizers in Manado. This research type is a causal type of research. It also called as explanatory research. This study held in the people of Manado, on August-September 2016. The sample in this research are customer in Wedding Organizer in Manado especially in students at FEB UNSRAT Manado. Samples of this research are 45 respondents. Data analysis method used validity and reliability test, classical assumption test, regression analysis model with hypotesis testing using t test and F test. Based on the results of hypothesis testing in particular the model of the research found that the research model consisting of: corporate image, and perceived value has a positive and significant influence on customer satisfaction simultaniouslly. Corporate image has significant and positive impact on customer satisfaction on wedding organizer customers in Manado partialy. Perceived value also has significant and positive impact on customer satisfaction on wedding organizer customers in Manado partialy. Perceved value become the most highest impact on customer satisfaction followed by corporate image in the second. This model applies on wedding organizer customer in Manado. Recommendations are: Wedding organizer need to pay attention and focus the company's marketing strategy effectively and efficiently. Other researchers are focusing on the research field of management science and the science of marketing management needs to pay attention to these findings by replicating the results of this research on the object of other research in other Internet-based companies.Keywords: corporate image, perceived value, customer satisfaction, wedding oranizer